EP941 Synchronous ovarian and endometrial cancers; a 10-year retrospective review in a UK tertiary centre. (1st November 2019) - Fairley, H; Blake, D; Rundle, S; Fisher, A; O'Donnell, RL
Abstract : Introduction/Background: The epidemiology of synchronous ovarian (OC) and endometrial cancers (EC) is poorly understood with conflicting hypotheses. Prognosis is uncertain and there is a need to understand if it is advantageous for patients with concordant histology to be treated as two synchronous primaries or a metastatic single primary. There are significant clinical implications with either approach. This study aimed to: 1) describe the incidence and survival outcomes of synchronous primaries, 2) Consider survival outcomes to matched case-control cohorts. Methodology: All cases of synchronous OC and EC 2007–2017 were identified from the departmental database. Patient demographics alongside clinicopathological data were collated. Survival analysis using 1:1 case-controls for isolated OC and EC, matched for age, diagnosis year, FIGO Stage, histological subtype, grade and surgical outcome was undertaken. Results: 72 cases of synchronous cancers represented 3.6% of total OC and 2.7% of total EC cases in the study period. 39 (54%) presented with presumed/confirmed OC with asymptomatic incidental diagnosis of EC; whilst 46% presented with symptomatic, biopsy proven EC, with incidental diagnoses of tubo-ovarian (88%), or primary peritoneal cancer (12%). Concordant histological subtype was seen in 43 (60%) cases, of which 32 (74%) were endometrioid. ≥2 antigens in an IHC panel was discordant in 89% of such cases. Overall survival (OS) was worse in synchronous cases compared to EC case controls (p=0.0419), but no significant difference was observed between synchronous cases and OC controls (p=0.6235, log-rank). In OC cases with concordant EC morphology where endometrial metastases would have resulted in higher stage (n=19), subgroup analysis suggested improved OS in synchronous cases compared with higher stage OC controls (p=0.0282, Wilcoxon). Conclusion: Synchronous OC and EC cancers occur infrequently with significant challenge in cases with concordant histology. Survival analysis suggests at least equivalent prognosis to matched ovarian cancers. An expanded dataset is needed to establish treatment algorithms. Disclosure: Nothing to disclose.